Turning Knowledge Into Action at the Point‐of‐Care: The Collective Experience of Nurses Facilitating the Implementation of Evidence‐Based Practice. (24th June 2013) - Dogherty, Elizabeth J.; Harrison, Margaret B.; Graham, Ian D.; Vandyk, Amanda Digel; Keeping‐Burke, Lisa
ABSTRACT: Background: Facilitation is considered a way of enabling clinicians to implement evidence into practice by problem solving and providing support. Practice development is a well‐established movement in the United Kingdom that incorporates the use of facilitators, but in Canada, the role is more obtuse. Few investigations have observed the process of facilitation as described by individuals experienced in guideline implementation in North America. Aim: To describe the tacit knowledge regarding facilitation embedded in the experiences of nurses implementing evidence into practice. Methods: Twenty nurses from across Canada were purposively selected to attend an interactive knowledge translation symposium to examine what has worked and what has not in implementing evidence in practice. This study is an additional in‐depth analysis of data collected at the symposium that focuses on facilitation as an intervention to enhance evidence uptake. Critical incident technique was used to elicit examples to examine the nurses' facilitation experiences. Participants shared their experiences with one another and completed initial data analysis and coding collaboratively. The data were further thematically analyzed using the qualitative inductive approach of constant comparison. Results: A number of factors emerged at various levels associated with the successes and failures of participants' efforts to facilitate evidence‐based practice. Successful implementation related to: (a) focus on a priority issue, (b) relevant evidence, (c) development of strategic partnerships, (d) the use of multiple strategies to effect change, and (e) facilitator characteristics and approach. Negative factors influencing the process were: (a) poor engagement or ownership, (b) resource deficits, (c) conflict, (d) contextual issues, and (e) lack of evaluation and sustainability. Conclusions: Factors at the individual, environmental, organizational, and cultural level influence facilitation of evidence‐based practice in real situations at the point‐of‐care. With a greater understanding of factors contributing to successful or unsuccessful facilitation, future research should focus on analyzing facilitation interventions tailored to address barriers and enhance facilitators of evidence uptake.